The Analyzing Online Learning Satisfaction and The Use of LLS: The investigation of students' satisfaction towards the frequent use of LLS - pietra dorand (Journal of Informatics and Communication Technology (JICT), 2020)
This mixed-method approach study is conducted to find out the positive relationship between students’ satisfaction and their LLS use in the context of ICT for ELL. Having wed out for the sake of validity and reliability, 46 sets of both SERVQUAL and SILL questionnaires were then administered to 83 students of telecommunication engineering at Akademi Telkom Jakarta. The result of the study was explained in inferential and descriptive as well as qualitative in nature. The statistical result confirmed the positive effect of online learning satisfaction on the use of LLS. The low correlation coefficient is detected between students’ satisfaction and the use of LLS (r =.235, p <.05); however, the regression model Y=74.3+0.20X is then eligible to estimate and generalize. Thus, by paying attention to SERVQUAL dimensions, the students will more explore their LLS use. The findings provide a greater understanding of students’ satisfaction and LLS use. LLS – CALL integration model could be developed as the implications of the research for further study. Keywords: ICT, Language Learning Strategies, Online Learning, Student Satisfaction, SERVQUAL